A 2000-year record of phosphorus forms and accumulation in peatland of the Greater Khingan Mountains in Northeast China: Paleoenvironmental implications. (10th October 2020) - Li, Yunhui; Han, Dongxue; Gao, Chuanyu; Liu, Hanxiang; Cong, Jinxin; Yu, Xiaofei; Wang, Guoping
Abstract: To investigate the connection of phosphorus (P) forms with peatland succession and history of fire in Tuqiang peatland, a 57 cm peat core was sampled with high-resolution (1-cm intervals) in the north of the Great Khingan mountain (Northeast China). AMS 14 C dating techniques combined with sequential chemical extraction was used to determine and calculate the accumulation rates of phosphorus fractions. Phosphorus forms were mainly composed with NaOH-Po, hot concentrated HCl–P (conc. HCl–P) and residual-P. Active phosphorus pools were enriched in the top 8–10 cm of the peat surface. The concentrations of organic phosphorus forms and residual-P were generally high during 1200 to 500 cal yr BP, and the accumulation rate of that gradually decreased since 1600 cal yr BP. Both of concentration and accumulation of organic phosphorus decreased after 600 cal yr BP. The accumulation rate of organic phosphorus forms significantly corresponded with peat development frequency, pollen records and other paleo evidence. The concentration and accumulation of organic phosphorus, especially NaOH-Po, was positively connected with concentration of pollen and Cyperaceae, and decreased when relative abundance of moss or shrubs occurred. Fire changed the vegetation community, decreased the concentration and accumulation of Po, and reduced inactive Po /Pi at the same time. Fire events could also leave geochemical evidence on peat. It is necessary to consider the both changes of inactive Po /Pi and organic phosphorus accumulation rate when reflected the fire history by phosphorus in core.